Developing indicators for intangible performance in values-based assessment for courses in CELPAD - Anuar, Siti Zubaidah; Abdullah, Liza; Kassim, Rosnani (CELPAD Research Unit, CELPAD, IIUM, 2023)
Humanising education in higher education requires the inculcation of values into its academic programmes. At the International Islamic University Malaysia, the introduction of the Sejahtera Academic Framework (SAF) is a move towards realising its mission of producing a holistic graduate or Insan Sejahtera through spirituality and values-driven education. Values are the intangibles, however, the current assessments at the university are centred around the tangibles where students are mostly evaluated in terms of their knowledge in specific subjects. Measurement tools for measuring the intangibles are still under- developed at the IIUM (International Islamic University Malaysia). Therefore, with the aim to develop a way to measure values that are intangible, this study is the first phase of the research conducted to explore the course instructors’ interpretations of values (the intangibles) that are essential in working collaboratively and how they see the values are manifested in students’ behaviour. This paper referred to the 7 Missions of IIUM, highlighting in the Islamic values and principles. 10 language nstructors of a writing course (which is a university required course) at CELPAD took part in this study. A qualitative method research design is employed for this study. Data were collected through Focus Group Discussions (FGD) among the instructors. The qualitative data from the FGDs (Focus Group Discussions) went through analyses via ATLAS.ti. Version 22. At the end of the study, the values were identified and grouped according to the Malaysian Qualification Framework (2017) under Cluster 3: Functional work skills (interpersonal and communication skills; leadership, autonomy and responsibility, Cluster 4: Personal and Entrepreneurial Skills and Cluster 5: Ethics and Professionalism. The study also found that there are some values that are not in the framework such as self-worthiness and determination. A checklist of values (the intangibles) expected from the students while doing their collaborative work is suggested to complement the existing scores which are represented by grades (tangible measurement) that students obtained for the course. By having these, it provides a holistic way to measure students’ achievement in doing their collaborative work.